2020
DOI: 10.1021/acs.jafc.0c01900
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembling Cyclodextrin-Based Nanoparticles Enhance the Cellular Delivery of Hydrophobic Allicin

Abstract: Most chemotherapeutics are hydrophobic molecules and need to be converted into hydrophilic formulations before administration. To address this issue, a novel cyclodextrin-based nanoparticle was proposed as a versatile carrier for cellular delivery of hydrophobic molecules. First, the effect of the polylysine (PL)/NH2-β-cyclodextrin (NH2-β-CD) ratio on particle size and encapsulation efficiency in prepared complexes was investigated. Subsequently, transmission electron microscopy images showed that the sizes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…To address this issue, He and co-workers reported that CD-based nanoparticles could be used as a multifunctional carrier for the enhanced cellular delivery of the hydrophobic compound allicin. 272 Positively charged polylysine (PL) was attached to NH 2 -β-CD to synthesize the amphiphilic PL/NH 2 -β-CD carrier, which facilitated cellular uptake by using the high affinity of PL for negatively charged cell membranes. Compared with the parent β-CD (Fig.…”
Section: Assemblies Of Charged Cds and Guestsmentioning
confidence: 99%
“…To address this issue, He and co-workers reported that CD-based nanoparticles could be used as a multifunctional carrier for the enhanced cellular delivery of the hydrophobic compound allicin. 272 Positively charged polylysine (PL) was attached to NH 2 -β-CD to synthesize the amphiphilic PL/NH 2 -β-CD carrier, which facilitated cellular uptake by using the high affinity of PL for negatively charged cell membranes. Compared with the parent β-CD (Fig.…”
Section: Assemblies Of Charged Cds and Guestsmentioning
confidence: 99%
“…Cyclodextrin (CD) is a cyclic oligosaccharide obtained from starch by enzymatic hydrolysis, mainly containing 6, 7 and 8 glucopyranose units forming α-CD, β-CD, and γ-CD respectively. α-, β- and γ-CD have hydrophobic cavities with internal diameters of approximately 0.47–0.53, 0.60–0.65 and 0.75–0.83 nm, respectively. Hydroxyl groups within the cyclodextrins are not only responsible for aqueous solubility but also allow the hydroxyl groups to interact with the hydrophilic components, making the hydrophobic drugs water-soluble complexes. In this inclusion complexation phenomenon, multiple cyclodextrin fragments can be involved by encapsulating one or more guest molecules, which can form a variety of complexation phenomena such as 1:1, 1:2, 2:2, etc. Therefore, this section is divided into three main sections on cyclodextrin-inclusive drugs, focusing on (1) natural cyclodextrin-inclusive drugs, (2) modified cyclodextrin-inclusive drugs and (3) cyclodextrin polymer-inclusive drugs.…”
Section: Cyclodextrin Nanodrug Carriers Based On Host–guest Systemmentioning
confidence: 99%
“…However, the modification process required the use of organic chemicals, complicated procedures, and long reaction times, which reduces its commercial viability. In another study, Chen et al 39 synthesized a chemically modified β-CD as a host molecule for a hydrophobic drug (20(S)-protopanaxatriol) and reported that the water dispersibility of the drug increased around 532-fold after encapsulation. Nevertheless, the preparation procedure used in that study to create the modified β-CD also involved the use of organic solvents and was relatively time consuming.…”
Section: Ds and Component Analysis Of Sacdmentioning
confidence: 99%